Bipolar Type 1 Disorder Comorbid with Idiopathic Epilepsy in Children: A Case Report - Syaiful Fadilah; Fatimah Haniman (HM Publisher, 2021)
Intoduction. Bipolar disorder in children and adolescents, is a clinical disorder that causes public mental health problems that need attention. In the last decade, bipolar disorder in children and adolescents has become a field of great interest, both in the clinical field and in research, especially in terms of the diagnosis which is still controversial. This case report aims to describe type 1 bipolar disorder in children accompanied by idiopathic seizures. Case presentations. A boy, Mr. M, 10 years old, came to the polyclinic with the chief complaint of walking around during lessons. From the autoanamnesis, the patient said that he was happy, had good achievements in school. The patient experienced a change in behavior for 1 year, which had worsened for 4 months ago. The patient walks around the school while the other students are studying, the patient can't sit still and feels bored. Patients sometimes sing while banging the table. About a week of changing behavior, the patient began to experience frequent seizures. The patient has seizures while sleeping, has seizures if during the day the patient is angry with other people or has too much activity. The patient received pharmacological therapy in the form of aripiprazole, valproic acid and lorazepam. Non-pharmacological interventions are given in the form of family psychoeducation about the disease suffered by the patient. Conclusion. Clinical and phenomenological characteristics of bipolar disorder in children and Teenagers are unique. In connection with the presence of a unique clinical picture, it is necessary to introduce cases and treatment as early as possible.